NIKAH SIRI DAN NIKAH KONTRAK DALAM PERSPEKTIF HUKUM POSITIF INDONESIA - Indira Acintya Hapsari; Rofiatul Mahmudah (Journal of Law, Society, and Islamic Civilization, 2014)
This research attempts to find out the form of underhand marriage and contract marriage committed widely in Indonesia and also to know contract marriage in Indonesian positive law perspective.The research methode employed was normative law research because studies the positive law rule. This study uses primary data source in the Law verses of holly Quran, the book of law and the Civil Law Act 1 of 1974 about marriage. This Study uses methodological approach.It can be found that underhand marriage ispermissible under Islamic law perspective but the Indonesian positive law perspective under handmarriage is contrary to theprovisions ofIndonesian laws.BecausetheIndonesian law, especially thatcontainedinLaw No.1of 1974onMarriage, terms of validity ofmarriageisone of themlistedaccording tothe rulesandregulationsapplicable. Marriagewith a termor commonlycalled thecontract marriageiscontrary to thephilosophy ofthe purposeof marriage. This is also supportedbythe positivelawprovision inthe agreementthat thevalidity ofone of them isbecause of thereasonthat is notillegal. While therelationship withmarriagecontracts, therelevant provisions"are not forbiddenbecause"not met. So thelegalmarriage contractcan not beaccepted as avalid agreement.